consider the given equations

-5x-2y=1----(1)

2x-11y=-83---(2)

Multiply in equation (1)by(2) and multiply in equation (2)by 5

2(-5x-2y)=1---(2)

-10x-4y=2---(3)

and

5(2x-11y)=-83(5)

10x-55y=-415(4)

-10x-4y+10x-55y=2-415

-59y=-413

\(y=(413)/(59)\)

=7

put value of y=7 in equation(1)

-5x-2(7)=1

-5x-14=1

-5x=1+14|

-5x=15

x=-3

-5x-2y=1----(1)

2x-11y=-83---(2)

Multiply in equation (1)by(2) and multiply in equation (2)by 5

2(-5x-2y)=1---(2)

-10x-4y=2---(3)

and

5(2x-11y)=-83(5)

10x-55y=-415(4)

-10x-4y+10x-55y=2-415

-59y=-413

\(y=(413)/(59)\)

=7

put value of y=7 in equation(1)

-5x-2(7)=1

-5x-14=1

-5x=1+14|

-5x=15

x=-3